2009
DOI: 10.1259/dmfr/51064053
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying fibroma in a Hong Kong community: the clinical and radiological features and outcomes of treatment

Abstract: OF in this community predominantly affects females. Although gynaecological history was not included in the clinical notes, there is a clear possibility of reactivation of OF growth at the menopause. Other potentially important contributing factors are "traditional Chinese medicine" and the progressive reduction in the degree of water fluoridation. Although most patients were followed up, this was only for a few years. Nevertheless, one case actually recurred during follow-up. Therefore, patients with OF shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…lesions found in older adults show a mixed pattern while a radiolucent pattern is frequently found with younger patients. 2 A similar observation was also espoused by Liu et al 5 in a recurrent case of OF, with the radio-graphic pattern changing from unilocular to multilocular and then to a radio-opaque lesion. Of the 20 cases examined separately by MacDonald-Janowski and Li 2 and Liu et al, 5 only a single case in each study showed a multilocular but radiolucent lesion: in a 26-year-old female and 12-year-old female, respectively.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…lesions found in older adults show a mixed pattern while a radiolucent pattern is frequently found with younger patients. 2 A similar observation was also espoused by Liu et al 5 in a recurrent case of OF, with the radio-graphic pattern changing from unilocular to multilocular and then to a radio-opaque lesion. Of the 20 cases examined separately by MacDonald-Janowski and Li 2 and Liu et al, 5 only a single case in each study showed a multilocular but radiolucent lesion: in a 26-year-old female and 12-year-old female, respectively.…”
Section: Discussionsupporting
confidence: 68%
“…4 Liu et al, 5 in an analysis of 20 Chinese patients with OF, found no gender significance compared with exclusive female involvement in 24 patients of Hong Kong Chinese descent. 2 The mean age also differed between these two Chinese groups, being 28 years (range 6-57 years) for Chinese and 38 years (range 10-80 years) for Hong Kong Chinese for both the maxillary and mandibular locations. However, both studies observed that patients with maxillary lesions were a decade younger at presentation than those with mandibular lesions.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations